Soybean roasting using continuous solar roaster–A decentralized approach for agricultural processing. (23rd July 2019) - Raza, Ali; Munir, Anjum; Ghafoor, Abdul; Ali, Shoukat
Abstract: The study was carried out to evaluate the performance of a continuous solar roaster for the roasting of soybeans. The system comprises a 10 m 2 fixed focus concentrator coupled with the continuous solar roasting system which is designed for decentralized processing of agricultural products in medium to high temperature range. The independent variables of roasting time (10–30 min) and temperature (140–160°C) were optimized for soybean roasting using response surface methodology. The optimized roasting conditions were found to be 29 min and 160°C at which urease activity was decreased to 0.09 ΔpH, protein solubility decreased to 80.76% and protein dispersibility index decreased to 28.53%, which inferred quite satisfactory performance for continuous solar roaster for soybean roasting in terms of quality. Moreover, moisture and fat contents were reduced by 86.3 and 29.9%, respectively whereas protein, fiber, carbohydrate and ash contents were increased by 12.9, 10.6, 8.1, and 14.1%, respectively after roasting. It was also concluded that 100 kg soybean can be roasted successfully on a sunny day with average direct normal irradiance ranging between 600 and 800 W m −2 . The payback period of continuous solar roaster was estimated to be 1.3 years in terms of fuel savings. Practical applications: Roasting of perishable agricultural products by concentrating solar power is a novel research area of solar thermal energy utilization in medium to high temperature range agricultural processing. A prototype of a continuous solar roaster (CSR) was developed that was fitted with a 10 m 2 elliptical fixed focus concentrator and a copper coil heat receiver coupled with the roasting unit. The CSR can generate a temperature >200°C for roasting with available direct normal irradiance (DNI) of 600–800 Wm −2 during the peak hours on a sunny day, thus capable of roasting a variety of agricultural products between 150 and 220°C. The farmers can install CSR at farm‐gate level for commercialized value addition as it is completely independent from fossil fuel based energy supplies for thermal and electric energy generation. Significant socio‐economic benefits could be realized for small to medium scale rural farming communities with this decentralized and eco‐friendly technology particularly in developing countries.